The Odyssey of History in Times of Memory: From the Song of the Sirens to the Robe of Penelope - Porras Mendoza, Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article investigates the role of history in memory. It attempts to resolve the questions: who remembers a past full of atrocities and pain, how can this be done, and for what reasons? This analysis is centered on two main categories: memory and history, including both their differences and their similarities. It scrutinizes the relationships between historiography, historical memory and contemporary politicalviolence speciically within the Colombian context, as well as the necessity and moral duty of society to engage in the exercise of memory with the maximum rigor and precision. In addition, this article will argue in favor of present-day history and subaltern studies. These historiographical trends are not only useful in articulating memory and history, but also in addressing and projecting the outlook of the victims in the asymmetrical and complex power relations that characterize Colombia.